Islamic Institution Students and Understanding Multiculturalism (Case Study at Institut Agama Islam Tarbiyatut Lamongan) - Farokhah, Fiqih Aisyatul (Proceedings of Annual Conference for Muslim Scholars, 2022)
This research aims to analyze the understanding of Islamic college students toward multiculturalism. Some of the problems studied are (1) the reasons for the importance of studying multiculturalism for students, (2) the forms of planting multiculturalism values based on Islamic religion for students of the Islamic Institute Tarbiyatut Tholabah (Tabah) Lamongan (3) the implications of multiculturalism on the understanding of IAI Tabah students about multiculturalism. This study uses qualitative data analysis methods. Multiculture already exists in Islamic teachings called Tasamuh. Tasamuh is a mubalaghah from samaha which means tolerance. Tasamuh is an open attitude that recognizes the diversity of ethnic groups, races, skin colors, languages, customs, cultures, languages, and religions. Multicultural education must include the concepts of diversity, respect, justice, tolerance, racism, prejudice, discrimination, and stereotypes. The results show that multiculturalism is important to be taught to students to realize Islamic moderation or Wasathiyah Islam. Activities are directed to support the multiculturalism of campus life. However, IAI Tabah students' understanding of multiculturalism is diverse.